Differences in Wall Shear Stress Between High-Risk and Low-Risk Plaques in Patients With Moderate Carotid Artery Stenosis: A 4D Flow MRI Study - Zhang, Guiling; Zhang, Shun; Qin, Yuanyuan; Fang, Jicheng; Tang, Xiangyu; Li, Li; Zhou, Yiran; Wu, Di; Yan, Su; Liu, Weiyin Vivian; Zhu, Wenzhen (Frontiers in Neuroscience, 2021)
This study aimed to evaluate the difference in wall shear stress (WSS) (axial, circumferential and 3D) between high-risk and low-risk plaques in patients with moderate carotid artery stenosis and to identify which time points and directions play the dominant role in plaque risk. Forty carotid arteries in thirty patients were examined in this study. All patients underwent high-resolution vessel wall (HRVW) imaging, DWI, and 4D flow MRI. Twenty-four high-risk plaques and sixteen low-risk plaques were enrolled. The independent sample t test was used to compare WSS between low- and high-risk plaques in the whole cardiac cycle, as well as at 20 different time points in the total cardiac cycle. The study found patients with high-risk plaques had higher WSS than low-risk plaques throughout the entire cardiac cycle (P < 0.05), but the changes varied at 20 different time points. The number of insignificant difference (P > 0.05) was less in diastole than systole in different time points. Axial WSS values were higher than circumferential WSS values; the difference in axial WSS values between high- and low-risk plaques was more significant than circumferential WSS, whereas 3D WSS values best reflected the difference between high-risk and low-risk plaques because they showed significant differences at every time point. In Conclusion, increased WSS, especially during diastolic period and in the axial WSS direction, may be related to high-risk plaque condition and cause cerebrovascular events in patients with moderate carotid artery stenosis. Also, these can provide hemodynamic information and help clinicians make more accurate decisions for plaque patients.